2010
DOI: 10.1007/s11250-010-9530-5
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of (co)variance components and genetic parameters for growth traits of Avikalin sheep

Abstract: (Co)variance components and genetic parameters for various growth traits of Avikalin sheep maintained at Central Sheep and Wool Research Institute, Avikanagar, Rajasthan, India, were estimated by Restricted Maximum Likelihood, fitting six animal models with various combinations of direct and maternal effects. Records of 3,840 animals descended from 257 sires and 1,194 dams were taken for this study over a period of 32 years (1977-2008). Direct heritability estimates (from best model as per likelihood ratio tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
13
2
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 21 publications
10
13
2
3
Order By: Relevance
“…Such appropriate selective procedure requires accurate (co)variance components and genetic parameter estimates. Genetic parameters for growth traits of different sheep breeds have been reported (Prince et al 2010, Di et al 2011, Abegaz et al 2010. The results of these studies have shown that the inclusion of maternal effects on the models considered for genetic analysis of growth traits, especially for pre-weaning traits, is of crucial importance.…”
Section: Introductionmentioning
confidence: 99%
“…Such appropriate selective procedure requires accurate (co)variance components and genetic parameter estimates. Genetic parameters for growth traits of different sheep breeds have been reported (Prince et al 2010, Di et al 2011, Abegaz et al 2010. The results of these studies have shown that the inclusion of maternal effects on the models considered for genetic analysis of growth traits, especially for pre-weaning traits, is of crucial importance.…”
Section: Introductionmentioning
confidence: 99%
“…Studies with different sheep breeds have shown that both direct and maternal genetic effects act on lambs' growth performance (MARÍA et al, 1993;SNYMAN et al, 1995;MANDAL et al, 2006a, b;PRINCE et al, 2010), thus, to achieve greater genetic progress in selection programs and increased accuracy in estimates, both components need to be considered in genetic models (MEYER, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Nota-se ainda que os coeficientes de herdabilidade materna estimados para PN e PD apresentaram magnitudes baixas, a partir do modelo mais apropriado. Para PN, o valor encontrado foi semelhante ao reportado por Matika et al 16 (0,12±0,03), e superior aos obtidos por Kushwaha 2 (0,09±0,04) e Prince et al 3 (0,08±0,03). Em artigo de revisão, Safari et al 17 relataram que as estimativas de herdabilidade materna para peso ao nascer para raças de dupla aptidão (carne e lã) variam entre 0,18 e 0,24.…”
Section: Resultsunclassified
“…Em artigo de revisão, Safari et al 17 relataram que as estimativas de herdabilidade materna para peso ao nascer para raças de dupla aptidão (carne e lã) variam entre 0,18 e 0,24. Já para PD, os coeficientes geralmente apresentam menores magnitudes conforme encontrado em outros trabalhos realizados com diferentes raças de ovinos, como 0,10 17 , 0,08 7 e 0,01±0,01 3 , observado também no presente estudo. A diminuição da importância dos efeitos maternos sobre os pesos dos cordeiros com o aumento da idade do animal é esperada 18,19 , apresentando importância em mamíferos, sobretudo em animais jovens 20 .…”
Section: Resultsunclassified
See 1 more Smart Citation